Приключения медвежонка - Гурина Ирина Валерьевна (Познаем мир вокруг нас, 2015)
Экземпляры: (20191017) / Инвентарный номер: 39652 / Цена: 46.50 / Сис.шифр: Д / Авт.знак: Г 95 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6